Metabolome analysis reveals flavonoid changes during the leaf color transition in Populus × euramericana ‘Zhonghuahongye’ - Chen, Mengjiao; Chang, Cuifang; Li, Hui; Huang, Lin; Zhou, Zongshun; Zhu, Jingle; Liu, Dan (Frontiers in Plant Science, 2023)
To investigate the mechanism of leaf colour change at different stages in Populus × euramericana ‘Zhonghuahongye’ (Poplar ‘Zhonghong’), leaf colour phenotypes were determined and a metabolomic analysis was performed on leaves at three stages (R1, R2 and R3). The results showed that the a*, C* and chromatic light values of the leaves decreased by 108.91%, 52.08% and 113.34%, respectively, while the brightness L values and chromatic b* values gradually increased by 36.01% and 13.94%, respectively. In the differential metabolite assay, 81 differentially expressed metabolites were detected in the R1 vs. R3 comparison, 45 differentially expressed metabolites were detected in the R1 vs. R2 comparison, and 75 differentially expressed metabolites were detected in the R2 vs. R3 comparison. 10 metabolites showed significant differences in all comparisons, which were mostly flavonoid metabolites. The metabolites that were upregulated in the three periods were cyanidin 3,5-O-diglucoside, delphinidin, and gallocatechin-gallocatechin, with the largest proportion consisting of flavonoid metabolites, and the primary downregulated metabolite was malvidin 3-O-galactoside. The shift of red leaves from a bright purplish red to a brownish green was associated with the continuous downregulation of malvidin 3-O-glucoside, cyanidin, naringenin, and dihydromyricetin. In this paper, we analysed the expression of flavonoid metabolites in the leaves of Poplar ‘Zhonghong’ at three stages and identified key metabolites closely related to leaf colour change, which has provided an important genetic basis for the subsequent genetic improvement of this cultivar.